Long-term Spectral Monitoring of Active Asteroid (6478) Gault: Implications for the H Chondrite Parent Body - Adam Battle; Vishnu Reddy; Juan A. Sanchez; Neil Pearson; Benjamin N. L. Sharkey; Theodore Kareta (The Planetary Science Journal)
Active asteroid (6478) Gault underwent outbursts between late 2018 and early 2019 with tails morphologically similar to the ejecta from Dimorphous following the Double Asteroid Redirection Test impact. Multiple studies investigated the dust properties, confirmed that Gault is an S-type Phocaea-family asteroid, and obtained a ∼2.5 hr rotation period consistent with being near the critical rotation period for breakup. We present results from near-infrared spectral monitoring of Gault on one night during a period of activity and five nights across 3 yr after activity ceased in order to understand the evolution of surface mineralogy over time. Spectral band parameters show an average Band I center of 0.920 ± 0.005 μ m, Band II center of 2.04 ± 0.13 μ m, and band area ratio of 1.33 ± 0.04. These values correspond to an olivine–pyroxene ratio of 0.40, 18.7 mol% fayalite, and 17.2 mol% ferrosilite—all of which are consistent with an H chondrite that has low levels of thermal metamorphism. Three meteorite analogs were identified that are H chondrites with petrologic types between H3.4 and H4. The low-level thermal metamorphism interpretation of Gault’s surface suggests that it formed from the outermost portion of the progenitor of the Phocaea family, assuming an “onion shell’ structure, which was catastrophically disrupted 1.2 Gyr ago. We discuss implications of Gault’s surface composition to better understand this H chondrite parent body, with the suggestion that more dynamical and spectral analyses be performed for members of the Phocaea family.